2017
DOI: 10.1128/aem.01540-17
|View full text |Cite
|
Sign up to set email alerts
|

Acyl-Homoserine Lactone Production in Nitrifying Bacteria of the Genera Nitrosospira, Nitrobacter, and Nitrospira Identified via a Survey of Putative Quorum-Sensing Genes

Abstract: The genomes of many bacteria that participate in nitrogen cycling through the process of nitrification contain putative genes associated with acyl-homoserine lactone (AHL) quorum sensing (QS). AHL QS or bacterial cell-cell signaling is a method of bacterial communication and gene regulation and may be involved in nitrogen oxide fluxes or other important phenotypes in nitrifying bacteria. Here, we carried out a broad survey of AHL production in nitrifying bacteria in three steps. First, we analyzed the evolutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(30 citation statements)
references
References 62 publications
1
29
0
Order By: Relevance
“…Comparing genomic features among Nitrospira strains, we first focused on the genes involved in nitrogen metabolism, such as nitrite reduction and urea degradation. Next, from the strain NJ1 genome, we discovered the key genes of acyl-homoserine lactone (AHL)-type quorum-sensing (QS) systems, which was reported in the previous study ( Nasuno et al, 2012 ; Mellbye et al, 2017 ), and we identified the chemical structures of the AHLs as autoinducers of strain NJ1. Moreover, the genome sequence of strain NJ1 lacks genes encoding bacterial flagella and CRISPR-Cas system, which were reported in genomic analyses of other Nitrospira ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Comparing genomic features among Nitrospira strains, we first focused on the genes involved in nitrogen metabolism, such as nitrite reduction and urea degradation. Next, from the strain NJ1 genome, we discovered the key genes of acyl-homoserine lactone (AHL)-type quorum-sensing (QS) systems, which was reported in the previous study ( Nasuno et al, 2012 ; Mellbye et al, 2017 ), and we identified the chemical structures of the AHLs as autoinducers of strain NJ1. Moreover, the genome sequence of strain NJ1 lacks genes encoding bacterial flagella and CRISPR-Cas system, which were reported in genomic analyses of other Nitrospira ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 96%
“…Recently, it was reported that the genome sequence of N. moscoviensis, N. inopinata , and Ca . Nitrospira nitrificans contains a gene encoding AHL synthase homologs ( Mellbye et al, 2017 ). Phylogenetic analysis based on the amino acid sequence of autoinducer synthases revealed that the LuxI homologs of Nitrospira were each clustered into single clades ( Figure 5 ), and that NjpI, a LuxI homolog in strain NJ1, was most closely related to that of Ca.…”
Section: Resultsmentioning
confidence: 99%
“…Other NOB have been documented to use quorum sensing at high cell densities and the Ca. Nitrotoga LuxI homolog grouped phylogenetically with other sequenced Betaproteobacteria [111,112]. Ca.…”
Section: Interactions With Other Organismsmentioning
confidence: 97%
“…Moreover, nitrifying bacteria do not produce enough EPS and barely achieved self-immobilization, so they were probably attached to EPS produced by other microorganisms. Since QS is responsible for bacteria communication and gene regulation during nitrification, the conditions in TB-EPS seem to be more favorable for nitrifying bacteria (Mellbye et al 2017).…”
Section: Bacterial Species and Eps Composition In Tb-epsmentioning
confidence: 99%